Mineralogical and ion-exchange leaching study of a Rare Earth Element (REE) bearing ion-adsorption clay deposit - Burcher-Jones, Cody Owen (Department of Chemical Engineering, 2019)
Rare earth elements (REEs), La to Lu including Y, are vital elements in manufacture of catalysts and metallurgical industries, and play a critical role in meeting future energy demands, such as through their use in permanent magnets in wind turbines. China has dominated more than 90 % of the REE market, with heavy REE (HREE) clay deposits in South China accounting for 35 % of their total REE output. This has prompted the evaluation of ion-adsorption clay (IAC) deposits in tropical regions outside China, namely Madagascar. Clay minerals such as kaolinite are part of the phyllosilicate class, containing structures of shared octahedral aluminium and tetrahedral silicon sheets. Isomorphous substitutions within the lattice leads to a charge imbalance, which accounts for negative charge on kaolinite, thus giving the ability to attract REE cations from aqueous solution to the surface of the clay particle. IAC deposits are formed from the tropical weathering of granite with REE enrichment from accessory minerals. IAC clay samples of two regolith profiles, the pedolith (A1) and saprock (A2, B and F) from northern Madagascar were collected and subjected to a suite of characterisation techniques to investigate the properties of the clay mineral. This included particle size distribution (PSD), X-ray fluorescence (XRF), X-ray diffraction (XRD), quantitative evaluation of minerals by scanning electron microscopy (QEMSCAN), inductively coupled plasma mass spectrometry (ICP-MS), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The geochemical leaching characteristics of the clay mineral were investigated using a sequential leaching program, targeting ion-exchangeable REE on kaolinite, halloysite, REEorganic matter and mineral phase. Ammonium sulphate leach experiments were conducted, varying the ionic strength to determine optimum leaching concentrations. Seawater is easily available at the coastal mine, therefore simulated seawater (NaCl) experiments were conducted with the addition of ammonium sulphate to improve the REE recovery. Compound leaching agents were investigated including varying magnesium / ammonium ratios in a sulphate system as well as ammonium in a varying nitrate / sulphate ratio system. The magnesium ion was investigated to correct the Mg deficiency in soils after leaching and the nitrate ion was investigated due to its high ionic permeability in kaolinite. Ion-adsorption clay leaching includes the leaching of impurities such as Al, Fe, Mg, K, Na, Ca and Mn. Ammoniumsulphate experiments with increasing amounts of ammonium acetate were conducted. Ammonium acetate acts a buffering agent to inhibit the leaching of the main impurity Al. The texture of sample A1 (5 to 6.5 m) was homogenous, with the QEMSCAN results showing Fe minerals distributed through the kaolinite, giving it a red appearance. The saprock samples A2, B and F have a heterogeneous texture due to the preservation of the primary texture. The QEMSCAN results show that this texture is composed of pure white kaolin, kaolin with red staining due to Fe minerals, tawny staining due to Al minerals and black phases containing Mn minerals. These Mn minerals show Ce deposited as the mineral cerianite, unavailable for ion-exchange. The pedolith sample was light REE (LREE) enriched but depleted in total REE (TREE = 1 503 ppm) compared with the saprock samples (TREE = 7 006 ppm on average). The saprock samples show LREE and HREE enrichment with samples A2 and F having La / Gd ratio of 17.4 and Gd / Lu ratios of 1.2. The more crystalline samples A2 and F (Hinckley index 0.40 and 0.44 respectively) are more REE enriched than the more weathered sample B (Hinckley index 0.32). The geochemical characterisation of sample A1 showed decreasing REE recovery from LREE to HREE from kaolinite whereas sample A2 showed consistent recovery across the REEs from kaolinite with both showing little Ce recovery. The best TREE recovery for samples A1 and A2 in the chloride system achieved with was NH4 + (44.3 % and 83.1 % respectively) followed by Na+ (39.5 % and 72.2 %) and Mg2+ (28.9 % and 72.1 % respectively). For sample A1 the recovery from the kaolinite fraction was 37.7 %, halloysite 5.1 %, organic 1.6 % and mineral 55.7 %. The proportion of ion-exchangeable REE is increased in sample A2 showing a recovery from the kaolinite fraction of 66.9 %, halloysite 12.7 %, organic 3.5 % and mineral 16.9 %. The results from increasing the ionic strength of ammonium sulphate shows that TREE leachant concentration increases as the concentration increases but decreases above 0.25 M. This indicates that the ammonium sulphate concentration saturates at 0.25 M and any further lixiviant increase eliminates access to the kaolinite surface. The simulated seawater experiments indicate that some addition of ammonium sulphate is beneficial as the addition of 0.05 M ammonium sulphate almost doubled the TREE leachant concentration. However excess addition of ammonium sulphate above 0.05 M had adverse effects on the leachant concentration of the LREEs. It was concluded from the compound leaching experiments that the Mg2+ ion can be used to supplement ammonium leaching with the greatest leachant concentration using a Mg2+:NH4 + ratio of 1:2 (equal charge). This ratio would produce a high REE leachant concentration while keeping Mg available for plants (flora). Compound leaching with the nitrate ion shows that the greatest REE leachant concentration was with a NO3 - :SO4 2- ratio of 2:1 (equal charge) due to increased nitrate ion permeability. The results from the addition of ammonium acetate as a buffer showed that the buffer inhibited the leaching of Al in both samples A1 and F, with the greatest inhibition at 0.05 M. The characterisation experiments illustrate the complexity of the in-situ clay deposit and further work should use this information to construct leaching models that take into account the heterogeneity of saprock samples. The leaching experiments show that compound leaching can improve REE recovery and further work should incorporate multiple lixiviants in in-situ leaching models.